Knowledge, Attitudes, and Practices in Relation to Reproductive Health Among Young Albanian Women - Alketa Zazo; Eliona Kulluri; Enxhi Vrapi (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: National and international health policies focus on improving the sexual and reproductive health among women, therefore, understanding the factors that motivate or refrain women from accessing reproductive health services is central to those policies. This study aimed to document the level of sexual health-related knowledge, attitudes, and practices among women of reproductive age (24-49 years old) in Tirana, Albania.